Passiflora virus Y in soybean: High susceptibility of soybean cultivars, unlikely transmission trough seeds and no detection of the virus in fields from São Paulo state, Brazil - da Cruz Martines, Caroline [UNESP]; Secler, Luana Cury [UNESP]; Favara, Gabriel Madoglio [UNESP]; de Oliveira, Cintia Sabino [UNESP]; Marubayashi, Julio Massaharu [UNESP]; Barreto da Silva, Felipe [UNESP]; Uzan, Juliana [UNESP]; Krause-Sakate, Renate [UNESP] (Springer Nature, 2024)
In 2020, the potyvirus passiflora virus Y (PaVY) was reported infecting soybean in Brazil. Considering its recent detection, little is known about the incidence of the virus in soybean-producing regions and if PaVY can be transmitted through seeds. The objectives of this study were to evaluated the reaction of soybean cultivars to PaVY infection (isolate PaVY-Br), assess the occurrence of PaVY in soybean crops in São Paulo state and investigate aspects related to its seed transmission and host range. An average, 40% of the seeds produced by infected plants exhibited symptoms of coat mottling. PaVY was not detected in 1219 seedlings originated from 811 non-mottled and 408 mottled seeds produced by PaVY-Br-infected soybean plants. The potyvirus was detected, by RT-PCR, on 9.8% of mottled and 37.7% of non-mottled seeds. PaVY-Br infected Canavalia ensiformis, Gossypium hirsutum, Nicotiana benthamiana, Phaseolus vulgaris, Raphanus sativus, and Vigna unguiculata, expanding the host range of this isolate. PaVY was not detected in 800 soybean samples collected from fields of this crop in 12 municipalities from São Paulo state during the crop seasons of 2021/2022 and 2022/2023. Overall, the results demonstrated high susceptibility of soybean cultivars mechanically inoculated with PaVY-Br, a low incidence of PaVY in soybean fields in the major producing regions of the state of São Paulo and that transmission of PaVY-BR through soybean seeds is unlikely.
Keywords: Glycine max; Host range; PaVY; Potyvirus